Grade 6 Mathematics Teachers Perceptions Of Pedagogical Variation With Information And Communication Technologies (Icts) In No-Fee Paying Schools: A Cultural Historical Activity Theory (Chat) Analysis - Tshink, Sakafuku (School of Education, 2020)
The South African education system is under a serious strain in relation to Mathematics attainment. Only 40% of learners in SA pass the final school leaving examination and only 5% of learners manage to pass Mathematics with more than 50%, according to The Economist (2014). In a bid to solve this problem the government proposes the use of ICTs (such as computer hardware and software, tablets, and smartphones) within teaching and learning. The assumption is ICTs can be utilised to address this important challenge and “facilitate ongoing improvement of educator skills” (The National Integrated ICT Policy White Paper: The White Paper, 2016: p.8). Research shows that teachers’ perceptions regarding the use of ICTs impact on their practices (Mwendwa, 2017; Munyengabe, Yiyi, He Haiyan, & Hitimana, 2017; Alharbi, 2012; Yuan & Chun-Yi Lee, 2012). This project intends to explore six grade 6 Mathematics teachers’ perceptions about whether and how pedagogy shifts with the use ICTs in the classrooms utilising Cultural Historical Activity Theory. This research utilises interviews as a method for the collection of empirical data to describe a group of research participants’ (or teachers’) perceptions who happen to be directly interviewed. These interviews have been conducted across two no-fee paying primary schools in the Western Cape Province (WCP), in South Africa (SA). Interviews were analysed along the CHAT dimensions: object, subject, tools, rules, community and division of labour to establish whether pedagogy altered along any of these dimensions. Findings indicate that teachers think pedagogy shifts in the ICT based lessons with division of labour becoming more fluid. Findings also show that the object of the activity system grows to encompass more than mere mathematical compression but also motivation, creativity and cognitive development. Besides, teachers stated that ICT based learning could assist learners in their mathematical attainment. This project is an investigation and not an intervention study. Recommendations are also suggested in this thesis for further research such as video-taping teaching and learning of mathematic contents and concepts in both traditional and computer-based classrooms. Further study in utilising classroom observations to focus on student-student interaction in relation to ICTs is also recommended.